Program ECO-Garden sebagai Implementasi Kampung Hijau Sebagai Pengembangan Zero Waste di Kelurahan Dermo (Proceedings of The National Conference on Community Engagement, 2026)
KKN-T Group 07 Dermo Village initiated an ECO-Garden program as a form of green village based on household waste management in Dermo Village. The ECO-Garden program integrates waste management with urban farming and Family Medicinal Plants (TOGA) activities. The analysis technique used in the community service article on the ECO-Garden program as the implementation of a Zero Waste-based Green Village in Dermo Village uses a descriptive analysis approach. This analysis was chosen because the main objective of service activities is to describe the program implementation process, level of community participation, changes in practice in the field, and achievement of activity output, not to test complex statistical relationships. The Eco Garden program is a form of implementing Green Village which is integrated with the zero waste concept. This program is not only oriented towards greening, but also aims to provide a simple solution to the plastic waste problem by reusing waste available in the surrounding environment.